Do nothing : how to break away from overworking, overdoing, and underliving - Headlee, Celeste Anne, 1969- (Harmony Books, 2020)
"We work feverishly to make ourselves happy. So why are we so miserable? Despite our constant search for new ways to "hack" our bodies and minds for peak performance, human beings are working more instead of less, living harder not smarter, and becoming more lonely and anxious. This manifesto helps us break free of our unhealthy devotion to efficiency and shows us how to reclaim our time and humanity with a little more leisure"--